Supervised machine learning framework for the analysis of contacting solids under inelastic strains - Flávio, Paulo Guilherme Marques (2023)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2023.